Collaborative Approaches to Enhancing Patient Care through Integrated Healthcare Roles in Saudi Arabia - Sultan Matar Althobaiti; Bandar Safar Alharthi; Mohammed Shaker Alotaibi; Abdul Majeed Abdullah Attian Al Thaqafi; Saad Omar Almalki; Rasheed Mohamed alharthi; Khalid Eidhaha Althagafi; Mohammed Al-Ahmari; Mosa Hassan Alfifi; Ibrahim Althomali; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Saudi Arabia’s healthcare system is undergoing a transformative shift under Vision 2030, emphasizing integrated care and patient-centered approaches to improve outcomes. Addressing the growing complexity of patient care—fueled by aging populations, multimorbidity, and chronic diseases—requires fostering interprofessional collaboration (IPC). Drawing on insights from global research, including the European Health Report 2012 and key studies on patient complexity, this paper evaluates the barriers and strategies for promoting IPC in Saudi Arabia. It emphasizes the importance of integrated roles, effective communication, role clarity, education, and supportive policies in achieving patient-centered care. With a focus on Saudi Arabia’s healthcare reforms, this paper highlights the need to align IPC efforts with cultural, organizational, and systemic factors to improve patient outcomes in the Kingdom.